Unity of Music and poetry in creation - ramin keshavarz; محب علی آبسالان (مطالعات ادیان و عرفان تطبیقی, 2018)
Harmony and animate cosmos has inspirited a particular idea to mystics that rhythmic movements of cosmos produce sound and each particle plays a tone, and the harmonious dance of cosmos begins. Contemplating in “Nomen” and inner substance of phenomena, mystics found the relation of music and poetry and perceived the beauty of these two arts. In each moment, they experienced musical order and cosmetic dance. They opposed those who considered cosmos as inanimate. With this attitude, they granted musical spirit to poetic appeal. Therefore, tools like music and poetry works like a passage from form to content and this is mysticism nature that abandons rational perception. The question is, is the music and poetry tools for sensual pleasures or spiritual growth? According to mystics, perceiving cosmetic order happens with diving at the depth of the nature. Therefore, art as a tool which formed in mystic soul was used for the discovery of facts. As a result, the music with absolute musical content and its simultaneity with poetry create transcendental art for mystic.